Zinc-finger antiviral protein inhibits XMRV infection. - Xinlu Wang; Fan Tu; Yiping Zhu; Guangxia Gao (PLoS ONE, 2012)
BACKGROUND: The zinc-finger antiviral protein (ZAP) is a host factor that specifically inhibits the replication of certain viruses, including Moloney murine leukemia virus (MoMLV), HIV-1, and certain alphaviruses and filoviruses. ZAP binds to specific viral mRNAs and recruits cellular mRNA degradation machinery to degrade the target RNA. The common features of ZAP-responsive RNA sequences remain elusive and thus whether a virus is susceptible to ZAP can only be determined experimentally. Xenotropic murine leukemia virus-related virus (XMRV) is a recently identified γ-retrovirus that was originally thought to be involved in prostate cancer and chronic fatigue syndrome but recently proved to be a laboratory artefact. Nonetheless, XMRV as a new retrovirus has been extensively studied. Since XMRV and MoMLV share only 67.9% sequence identity in the 3'UTRs, which is the target sequence of ZAP in MoMLV, whether XMRV is susceptible to ZAP remains to be determined. FINDINGS: We constructed an XMRV-luc vector, in which the coding sequences of Gag-Pol and part of Env were replaced with luciferase-coding sequence. Overexpression of ZAP potently inhibited the expression of XMRV-luc in a ZAP expression-level-dependent manner, while downregulation of endogenous ZAP rendered cells more sensitive to infection. Furthermore, ZAP inhibited the spreading of replication-competent XMRV. Consistent with the previously reported mechanisms by which ZAP inhibits viral infection, ZAP significantly inhibited the accumulation of XMRV-luc mRNA in the cytoplasm. The ZAP-responsive element in XMRV mRNA was mapped to the 3'UTR. CONCLUSIONS: ZAP inhibits XMRV replication by preventing the accumulation of viral mRNA in the cytoplasm. Documentation of ZAP inhibiting XMRV helps to broaden the spectrum of ZAP's antiviral activity. Comparison of the target sequences of ZAP in XMRV and MoMLV helps to better understand the features of ZAP-responsive elements.